TAXONOMY FOR WSN SECURITY-A SURVEY - Chaple, Kshitija Ajabrao (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
WSN is one of the dominant and emerging technology that shows great promise forÂ  various application in military, ecological and health related areas.WSN is highly vulnerable to attacks and inclusion of wireless communication technology incurs various types of security threats.WSN requires security measures due to sensitive data and as sensor may operate in hostile unattended environment.WSN suffer from constraints like low computational capability, small memory limited energy resources physical capture susceptibility and insecure wireless communication channel. These create security a challenge in WSN. In this article we provide a survey of security in WSN.We provide an outline with constraints and security requirement and attacks with their counter measures in WSN.